Neuroendocrine regulations in tissue-specific immunity: From mechanism to applications in tumor - Liu, Si-Qing; Li, Bei; Li, Juan-Juan; Sun, Si; Sun, Sheng-Rong; Wu, Qi (Frontiers in Cell and Developmental Biology, 2022)
Immune responses in nonlymphoid tissues play a vital role in the maintenance of homeostasis. Lots of evidence supports that tissue-specific immune cells provide defense against tumor through the localization in different tissue throughout the body, and can be regulated by diverse factors. Accordingly, the distribution of nervous tissue is also tissue-specific which is essential in the growth of corresponding organs, and the occurrence and development of tumor. Although there have been many mature perspectives on the neuroendocrine regulation in tumor microenvironment, the neuroendocrine regulation of tissue-specific immune cells has not yet been summarized. In this review, we focus on how tissue immune responses are influenced by autonomic nervous system, sensory nerves, and various neuroendocrine factors and reversely how tissue-specific immune cells communicate with neuroendocrine system through releasing different factors. Furthermore, we pay attention to the potential mechanisms of neuroendocrine regulation-tissue specific immunity axis involved in tumors. This may provide new insights for the immunotherapy of tumors in the future.